KNOWLEDGE INFLUENCE IN THE COMPLIANCE RATE OF TAKING DRUGS TUBERCULOSIS - Kamri Andi Maulana; Asmaliani Ira (Pharmacoscript, 2023)
Compliance with medication for tuberculosis patients is one of the determinants of the success of therapy in addition to the effectiveness of antibiotics. The aim of this study is to identify the factors that influence the success of a therapy, in the long-term use of antibiotics for tuberculosis. We use questionnaires that we have created and validated in interviews and can be used to directly measure the level of compliance with the therapy experienced by the patient. This research method is an observational study with cross-sectional design and retrospective data collection. Respondents were patients with tuberculosis, both new and recurrent. The study sample consisted of 30 respondents with sequential sampling selection and the basis for patient interviews. The analysis used is a Chi-square binary between a variable in the history of tuberculosis with a long diagnosis during therapy that shows a relationship between education and family involvement in helping treatment especially in male patients with a P value <0,05. Multivariate analysis showed that men who never completed education even though they were still in a productive age had a low level of compliance. The results of the interviews showed that patients who obeyed the drug only reached 30% with scores reaching a score of 8. This is due to the large amount of medication taken, so the risk of success of therapy is very large. This research shows that the level of education, information, and family environment can support patient medication compliance. In addition, the more the amount of medication taken, the lower the patient's compliance.